2019
DOI: 10.1016/j.physletb.2019.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Interior volume of Banados–Teitelboim–Zanelli black hole

Abstract: We calculate the interior volume for the three-dimensional Banados-Teitelboim-Zanelli black hole in this paper. To that end, we obtain the volume functional and numerically find a path to extremize it, before choosing a spacelike hypersurface to get an asymptotic analytical expression for the interior volume based on the characteristics of the path.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…The volume of this hypersurface defining the black hole volume increases monotonically with the advanced time v. As discussed by many [4,6,17,19,24], such a behaviour can be appropriately used in defining and understanding the black hole entropy. We will touch on this in latter sections.…”
Section: B Traceless Extrinsic Curvature Techniquementioning
confidence: 96%
“…The volume of this hypersurface defining the black hole volume increases monotonically with the advanced time v. As discussed by many [4,6,17,19,24], such a behaviour can be appropriately used in defining and understanding the black hole entropy. We will touch on this in latter sections.…”
Section: B Traceless Extrinsic Curvature Techniquementioning
confidence: 96%
“…The concept of simultaneity surface does not work in curved spacetime any more, so we are left with finding the extreme value of V Σ to obtain the interior volume of the black hole. Using Lagrangian method, it was found that the functional (13) can be extremal when the coordinate r of the two-dimensional surface S satisfies [8,13] dr(λ) dλ = 0.…”
Section: B Interior Volume and Entropy Of Black Holesmentioning
confidence: 99%
“…Here in (23), we have considered the retarded time v the black hole mass m as variations. The retarded time v is in fact v(λ f ) which denotes the end of the collapse, contrasting with v(λ i ), which corresponds to the beginning of the collapse [8,13]. v(λ i ) is the time that the horizon forms (which has been set to be zero in above).…”
Section: The Corrected Thermodynamics and The Interior Entropy For Bl...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [14], M. Zhang followed the CR work and found the interior volume of BTZ black hole increases with advance time. This work showed that the above stated discussion could be extended to (2 + 1)− dimensional BTZ black holes.…”
Section: Introductionmentioning
confidence: 99%